Ageing and Job Performance: Methodological Issues and Empirical Evidence (Malaysian Management Journal, 2000)
This article reviews the methodological difficulties involved in research on age and job performance, It also examines the empirical evidence of the relationship between age and job performance. Research in this area has been conducted in both laboratory as well as occupational settings. Research in occupational settings has generally utilized either output measures or performance evaluations to measure job performance. Evidence from the literature has generally found no conclusive relationship between age and job performance. Studies have also found experience rather than age predicts job performance to a greater extent than age.